1990
DOI: 10.1021/ie00103a042
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent three-phase azeotropic distillation. 3. Modern thermodynamic models and multiple solutions

Abstract: A new simulation method using an extended phase-stability and phase-splitting algorithm has been programmed, and new three-phase regions are identified in published azeotropic distillation examples.If phase splitting is ignored, then an erroneous composition profile can be produced. The modern thermodynamic models UNIFAC-VLE, UNIFAC-LLE, modified UNIFAC, UNIQUAC, NRTL, ASOG, and modified ASOG have been investigated in the simulation model. The sensitivity of the selection of thermodynamic model on temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…In this regard, Kingsley and Lucia (1988) and Widagdo et al (1989Widagdo et al ( , 1992 show that in place of stable three-phase (VLL) solutions, multiple two-phase (VL) solutions are often computed, each of which is unstable. Furthermore, Cairns and Furzer (1990~) show, for the dehydration of ethanol with 2,2,4-trimethylpentane, that spurious solutions are computed when the second liquid phase is not modeled. In many towers, stability analysis must be performed very carefully to properly solve the MESH equations.…”
Section: Mche Journal January1996mentioning
confidence: 99%
“…In this regard, Kingsley and Lucia (1988) and Widagdo et al (1989Widagdo et al ( , 1992 show that in place of stable three-phase (VLL) solutions, multiple two-phase (VL) solutions are often computed, each of which is unstable. Furthermore, Cairns and Furzer (1990~) show, for the dehydration of ethanol with 2,2,4-trimethylpentane, that spurious solutions are computed when the second liquid phase is not modeled. In many towers, stability analysis must be performed very carefully to properly solve the MESH equations.…”
Section: Mche Journal January1996mentioning
confidence: 99%
“…Their dynamic simulation results are consistent with the five steady states reported by Kovach and Seider (1987b). Cairns and Furzer (1990) study the multiplicities by Magnussen et al (1979) using the UNIFAC(VLE) model. Two of the steady states were obtained only by ignoring the phase splitting and hence they conclude that these profiles are fictitious.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Regarding azeotropic distillation operations, Bossen et al found four steady states for the dehydration of ethanol with benzene by dynamic simulation. 8 Also, Gü ttinger and Morari found two stable steady states caused by the vapor-liquid equilibrium for the ternary homogeneous methanol-methylbutyrate-toluene (MMT) system on an industrial pilot column.…”
Section: Introductionmentioning
confidence: 99%